Human Tumor Cell Proliferation Evaluated Using Manganese-Enhanced MRI - Braun, Rod D.; Bissig, David; North, Robert; Vistisen, Kerry S.; Berkowitz, Bruce A. (PLOS ONE, 2012)
Background Tumor cell proliferation can depend on calcium entry across the cell membrane. As a first step toward the development of a non-invasive test of the extent of tumor cell proliferation in vivo, we tested the hypothesis that tumor cell uptake of a calcium surrogate, Mn2+ [measured with manganese-enhanced MRI (MEMRI)], is linked to proliferation rate in vitro. Methodology/Principal Findings Proliferation rates were determined in vitro in three different human tumor cell lines: C918 and OCM-1 human uveal melanomas and PC-3 prostate carcinoma. Cells growing at different average proliferation rates were exposed to 1 mM MnCl2 for one hour and then thoroughly washed. MEMRI R1 values (longitudinal relaxation rates), which have a positive linear relationship with Mn2+ concentration, were then determined from cell pellets. Cell cycle distributions were determined using propidium iodide staining and flow cytometry. All three lines showed Mn2+-induced increases in R1 compared to cells not exposed to Mn2+. C918 and PC-3 cells each showed a significant, positive correlation between MEMRI R1 values and proliferation rate (p≤0.005), while OCM-1 cells showed no significant correlation. Preliminary, general modeling of these positive relationships suggested that pellet R1 for the PC-3 cells, but not for the C918 cells, could be adequately described by simply accounting for changes in the distribution of the cell cycle-dependent subpopulations in the pellet. Conclusions/Significance These data clearly demonstrate the tumor-cell dependent nature of the relationship between proliferation and calcium influx, and underscore the usefulness of MEMRI as a non-invasive method for investigating this link. MEMRI is applicable to study tumors in vivo, and the present results raise the possibility of evaluating proliferation parameters of some tumor types in vivo using MEMRI.